A critical and exegetical commentary on the Pastoral Epistles (I and II Timothy and Titus) - Lock, Walter 1846-1933. (Edinburgh, Scotland : T. and T. Clark, 1924)
Includes bibliographical references and indexes
Preface dated 1924; reprint.
Includes bibliographical references and indexes.
Keywords: Bible. -- commentaries